Rehabilitation of the Upper Extremity after Stroke: Current Practice As a Guide for Curriculum - Mylene Schriner PhD, OTR/L; Janell Thome OTR/L; Monica Carrier OTR/L (Scholarworks @ WMU, 2014)
Stroke is the leading cause of disability in the United States and a top diagnosis for occupational therapy (OT) services among neurological conditions. Academic programs teach OT students neurological frames of reference (FORs) to provide a foundation for future practice. To meet accreditation standards, entry-level curricula must reflect current practice and evidence-based interventions. A survey of OT practitioners working in upper extremity stroke rehabilitation was conducted to investigate current clinical practice in a variety of treatment settings. Survey questions probed the use of motor rehabilitation techniques exclusive to one of six neurological FORs: Brunnstrom, Constraint-induced Movement Therapy, Neurodevelopmental Treatment, Proprioceptive Neuromuscular Facilitation, Rood, and Task-Oriented. Responses from 167 OT professionals indicated interventions representing all six FORs are currently being utilized in stroke rehabilitation. Techniques from the Task-Oriented and Neurodevelopmental Treatment approaches were used most frequently; however, the Rood-based techniques were used much less than interventions from the other FORs. No single neurological approach was found to dominate practice regardless of the number of years of experience in stroke rehabilitation or years since graduation from an entry-level program. A majority of participants appear to employ techniques from multiple approaches frequently, suggesting contemporary OT practice in upper extremity stroke rehabilitation is eclectic in nature.